Vladimir Nabokov : the American years - Boyd, Brian, 1952- (Princeton University Press, 1991)
The story of Nabokov's life continues with his arrival in the United States in 1940. He found that supporting himself and his family was not easy--until the astonishing success of Lolita catapulted him to world fame and financial security.